1997
DOI: 10.1108/01425459710170095
|View full text |Cite
|
Sign up to set email alerts
|

Taiwanese labour management in China

Abstract: Interviews of 40 Taiwanese factory managers in China reveal problems with local workers, unanticipated because of the assumed shared language and culture. Problems include poor job commitment or work discipline, high turnover rates, disinterest in learning new skills or job advancement, pilferage, intergroup hostilities and poor training and education. Unable to import worker management methods and systems they had been using in Taiwan, the managers have adopted production‐based remuneration, fines, employee e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The new recruits, mainly female high school graduates in their late teens, had no previous working experience. While this facilitated indoctrination into Japanese corporate values, because they had no basis for making unfavourable evaluations of company rules and systems, prior literature has indicated that policies of hiring migrant workers have typically given rise to two problems: one concerning low skill levels and the other concerning 'home town loyalties' (Schak, 1997), with a tendency for workers from different counties or villages to group together. While it has usually been possible to remedy low skill levels relatively easily by means of various on-the-job training programmes, divided loyalties have posed a more serious challenge to the foreign companies, since the strong emotional bonds within the various subcultures among the migrant workers have tended to empower them to act collectively against managerial prerogatives and to resist the imposition of a corporate ethos (Smith & Pun, 2006).…”
Section: Cultural Transformation?mentioning
confidence: 99%
“…The new recruits, mainly female high school graduates in their late teens, had no previous working experience. While this facilitated indoctrination into Japanese corporate values, because they had no basis for making unfavourable evaluations of company rules and systems, prior literature has indicated that policies of hiring migrant workers have typically given rise to two problems: one concerning low skill levels and the other concerning 'home town loyalties' (Schak, 1997), with a tendency for workers from different counties or villages to group together. While it has usually been possible to remedy low skill levels relatively easily by means of various on-the-job training programmes, divided loyalties have posed a more serious challenge to the foreign companies, since the strong emotional bonds within the various subcultures among the migrant workers have tended to empower them to act collectively against managerial prerogatives and to resist the imposition of a corporate ethos (Smith & Pun, 2006).…”
Section: Cultural Transformation?mentioning
confidence: 99%
“…This was recognition in part of the need for increased flexibility in employment relations practices in a more open economy. At the same time, the internationalisation of the economy has included largescale Taiwanese investment in the PRC, with many Taiwan's managers having to learn new skills to manage mainland Chinese employees (Schak 1997).…”
Section: Taiwan: Decentralised Industrialisationmentioning
confidence: 99%
“…This was recognition in part of the need for increased flexibility in employment relations practices in a more open economy. At the same time, the internationalisation of the economy has included large-scale Taiwanese investment in the PRC, with Changing employment relations 309 many of Taiwan's managers having to learn new skills to manage mainland Chinese employees (Schak, 1997). Democratisation has in part led to the introduction of new social welfare legislation, such as unemployment insurance; however, its effect on the unions has been less clear.…”
Section: Taiwan: Decentralised Industrialisationmentioning
confidence: 99%
“…In another incident, a Taiwanese factory owner gave production-related bonuses to his better workers, but this backfired. Recipients were quite happy, but the others went on strike, saying that they would not work unless treated equally (Schak, 1997).…”
Section: Professional Relationship Versus Friendshipmentioning
confidence: 99%